Two Sides of the Same Coin—Explaining the Acceptance of CO2-Based Fuels for Aviation Using PLS-SEM by Considering the Production and Product Evaluation - Simons, Lisanne; Engelmann, Linda; Arning, Katrin; Ziefle , Martina (Frontiers in Energy Research, 2021)
In the present study, we studied the acceptance of CO2-based fuels for aviation as a product manufactured using Carbon Capture and Utilization (CCU). CCU can be regarded as the cornerstone for a circular approach. We focused on understanding whether the evaluation of CCU as a production method is related to the social acceptance of the resulting product. We applied an empirical quantitative approach using an online questionnaire targeted at German, Spanish, Dutch, and Norwegian respondents (N = 2,187). For both CCU and the fuel, lay perceptions in terms of perceived benefits and barriers were assessed, as well as their affective evaluation. Additionally, the acceptance of the end-product was surveyed. Using partial least squares structural equation modeling (PLS-SEM), we gained a better understanding of how the acceptance of CO2-based fuels for aviation is formed. We found that the evaluation of CCU was mainly indirectly related to the acceptance of the product through relationships with the evaluation of the fuels. The perception of the benefits of CCU did affect the benefit perception of CO2-based fuels the most, followed closely by the affective evaluation of the fuels. For the perception of the barriers of CO2-based fuels, the perceived barriers of CCU were again the strongest predictor, followed by the affective evaluation of the fuels. We identified a moderate predictive power for the acceptance of CO2-based fuels. The relationship with the perceived benefits of the fuels was the most relevant, followed by barrier perceptions, the affective evaluation of the fuels, and finally the benefit perception of CCU. Overall, the findings yield first insights into the role of the evaluation of CCU and CO2-based fuels for aviation for the formation of the product’s acceptance. The outcomes are useful for informing the product’s and CCU’s technical development and policy making. Additionally, they aid in the design of public information about CCU and support the development of sensible communication strategies for the successful market roll-out of CCU and CO2-based fuels.